Acute and subacute oral toxicity assessment of the polysaccharides extracted from Clinacanthus nutans leaves: a preclinical model for drug safety screening - Chia, Tan Yong; Gan, Chee Yuen; Kaur, Gurjeet; Cheah, Pike See; Murugaiyah, Vikneswaran; Ahmad, Ashfaq; Alsuwayt, Bader; Alnasser, Sulaiman Mohammed Abdullah; Shafie, Muhammad Hakimin; Nair, Selvamani Narayan; Abdulla, Mohammed H.; Johns, Edward James (Penerbit Universiti Sains Malaysia, 2025)
Emerging investigations have indicated that many plant polysaccharides may be beneficial for treating metabolic diseases. To date, the therapeutic efficacy and potential toxicity of polysaccharides extracted from Clinacanthus nutans (C. nutans) remain unexplored. This study investigated the in vivo acute and subacute oral toxicological profiles of the highest doses of C. nutans bioactive polysaccharides (CNBP) extracted from the leaves using conventional toxicity methods. The total of 39 healthy 8–10 weeks male Sprague-Dawley rats (n = 3) were randomly assigned to control (C), acute (A) and subacute (SA) groups receiving 125, 250, 500, 1,000, 2,000 or 3,000 mg/kg/day of CNBP extract, respectively. The acute group received a single dose of CNBP extract, whereas the subacute group received daily single doses of CNBP extract for 14 days. Oral administration of up to 3,000 mg/kg CNBP extract caused no abnormal signs of toxicity during 14 days. However, daily administration of 500 mg/kg or higher doses of CNBP extract for 14 days induced a mild degree of toxicity in the liver, characterised by elevated alkaline phosphatase levels with C (163 ± 9 U/L) vs. SA500 (222 ± 49 U/L), SA1000 (223 ± 29 U/L), SA2000 (238 ± 33 U/L) and SA3000 (252 ± 18 U/L). CNBP extracts exhibit therapeutic potential, exemplified by diuretic, natriuretic, anti-hypertensive, anti-tachycardia, reno-protective and cholesterol-lowering properties. Precautions should be taken when administering the extracts at higher doses and for longer durations.